Endothelial Dec1-PPARγ Axis Impairs Proliferation and Apoptosis Homeostasis Under Hypoxia in Pulmonary Arterial Hypertension - Li, Xiaoming; Liu, Chengcheng; Qi, Wenwen; Meng, Qiu; Zhao, Hui; Teng, Zhenxiao; Xu, Runtong; Wu, Xinhao; Zhu, Fangyuan; Qin, Yiming; Zhao, Miaoqing; Xu, Fenglei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: The hypoxia-induced pro-proliferative and anti-apoptotic characteristics of pulmonary arterial endothelial cells (PAECs) play critical roles in pulmonary vascular remodeling and contribute to hypoxic pulmonary arterial hypertension (PAH) pathogenesis. However, the mechanism underlying this hypoxic disease has not been fully elucidated. Methods: Bioinformatics was adopted to screen out the key hypoxia-related genes in PAH. Gain- and loss-function assays were then performed to test the identified hypoxic pathways in vitro. Human PAECs were cultured under hypoxic (3% O2) or normoxic (21% O2) conditions. Hypoxia-induced changes in apoptosis and proliferation were determined by flow cytometry and Ki-67 immunofluorescence staining, respectively. Survival of the hypoxic cells was estimated by cell counting kit-8 assay. Expression alterations of the target hypoxia-related genes, cell cycle regulators, and apoptosis factors were investigated by Western blot. Results: According to the Gene Expression Omnibus dataset (GSE84538), differentiated embryo chondrocyte expressed gene 1-peroxisome proliferative-activated receptor-γ (Dec1-PPARγ) axis was defined as a key hypoxia-related signaling in PAH. A negative correlation was observed between Dec1 and PPARγ expression in patients with hypoxic PAH. In vitro observations revealed an increased proliferation and a decreased apoptosis in PAECs under hypoxia. Furthermore, hypoxic PAECs exhibited remarkable upregulation of Dec1 and downregulation of PPARγ. Dec1 was confirmed to be crucial for the imbalance of proliferation and apoptosis in hypoxic PAECs. Furthermore, the pro-surviving effect of hypoxic Dec1 was mediated through PPARγ inhibition. Conclusion: For the first time, Dec1-PPARγ axis was identified as a key determinant hypoxia-modifying signaling that is necessary for the imbalance between proliferation and apoptosis of PAECs. These novel endothelial signal transduction events may offer new diagnostic and therapeutic options for patients with hypoxic PAH.